Effectiveness of Using the Klipaa.id Application for Delivering Lectures to Environmental Education Students in the Era of Artificial Intelligence - Ali Khan, Humair; Marlina, Ani; Cahyadi, Ani (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2025)
The aim of this research is to analyze the effectiveness of online and offline learning through the Klipaa.id application, as an online learning medium for Environmental Education class students at STKIP Kusuma Negara Jakarta in the Artificial Intelligent (AI) era. The method in this research is descriptive research with a qualitative approach and data collection techniques are carried out through interviews. Data validity using source triangulation. Data analysis techniques use the Miles and Huberman model, namely data collection, data reduction, data presentation, and drawing conclusions. The research results show that the use of the Klipaa.id application is very effective in terms of three indicators, namely in terms of the intensity of lecture implementation which can be utilized by students and lecturers, in terms of communication it can be seen from the use of features to receive and send lecture material neatly in the agenda feature, and in terms of fulfillment, it can be seen that students feel their information needs are met during online and offline lectures. Klipaa.id is only one media/application, there are many other media/applications that can optimize learning that takes place online and offline (blended learning).